SYMBOLIC MESSAGES OF KERAWANG GAYO’S TRADITIONAL PATTERNS - Muhsin Efendi; Viana Safrida Harahap; Hasan Basri (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2022)
The present study aimed to analyze the meaning of symbolic messages found in the Kerawang Gayo's traditional patterns and their applications into Gayo’s traditional clothing. The present study also discusses efforts needed to preserve Kerawang Gayo. The present research applied a historical and ethnographic approach. Data was collected through the processes of documentation, observations and interviews. The results of present study show 14 Kerawang Gayo’s patterns; (1) Tapak Sleman (Footprint of Sulaiman), (2) Tali Puter Tige (Rope Twisted Third Times) (3) Mata ni Lao (sun), (4) Pucuk ni Tuis (Bamboo Sprout), (5) Emun Berkunē (Fixed Clouds), (6) Emun Berangkat (Walking Clouds), (7) Peger (Fence), (8) Emun Beriring (Lining Clouds) (9) Rante (Chain) (10) Tali Mestike (Mustika’s Rope) (11) Tekukur (Measurement) (12) Cucuk Pengong (Circle) (13) Emun Mupesir (Splitting Cloud), (14) Sarak Opat (Four Elements In One Integrated Bond). The use of specific patterns and the colors of Gayo’s patterns depend on the wearer’s position in the society as Kerawang Gayo is regarded as a sacred item for people in Aceh.